Cross-border tax evasion after the common reporting standard: Game over? - Elisa Casi; Christoph Spengel; Barbara M. B. Stage (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2019)
We study the effect of the first global multilateral standard for the automatic exchange of information (AEOI), the so called Common Reporting Standard (CRS), on cross border tax evasion. Employing newly available bilateral data on cross-border deposits, we find that the CRS induced a reduction of 11.9% in cross-border deposits parked in traditional offshore countries for tax evasion purposes. Moreover, regardless of the 2,600 bilateral exchange relations created under the CRS, relocation is still a desirable option. More specifically, upon the CRS implementation at the domestic level, the United States, which so far did not commit to the CRS, seems to emerge as a potentially attractive location for cross-border tax evasion.
Keywords: F42; G21; H26; H31; 330; Tax Evasion; Automatic Exchange of Information; Offshore Countries; Cross-Border Deposits